Sometimes it helps: the evolving predictive power of spreads on GDP dynamics - Giulio Nicoletti; Raffaele Passaro (European Central Bank (ECB), 2012)
We investigate the predictive content of credit and government interest spreads with respect to the Italian GDP growth. Our analysis with Dynamic Model Averaging identifies when interest spreads were more useful predictors of economic activity: these periods are not limited to the Great Recession. For credit spreads we gather information from both bank loans and corporate bonds and we compare their predictive role over time and over different forecasting horizons.
Keywords: C52; E37; 330; Bayesian econometrics; GDP forecasting; model averaging